Does National Institute for Health and Clinical Excellence guidance identify all patients who will benefit from implantable cardioverter defibrillators?. (22nd September 2015) - Gall, SA; Kelland, NF; Neville-Smith, KE; W Lord, S; Plummer, CJ; McComb, JM
Abstract : Introduction: This study was to assess compliance with the National Institute for Health and Clinical Excellence (NICE) and more inclusive European Society of Cardiology (ESC) guidelines in patients who have received implantable cardioverter defibrillator (ICD) therapy, and to assess whether delivered anti-tachycardia therapy differed between those in whom ICD implantation complied and did not comply with NICE guidance. Methods: Consecutive patients who had an ICD implanted during the 18-month period from 1 July 2006 to 31 December 2007 were identified at one tertiary cardiology centre. A retrospective review of medical and device records was performed. The indication for ICD therapy was deemed compliant or not compliant using national (NICE) and ESC criteria as the audit standard. Electrograms recorded at the time of tachycardia therapy delivery were reviewed and therapy was classed as appropriate when electrograms confirmed ventricular tachycardia or ventricular fibrillation and inappropriate if there was sinus tachycardia or atrial arrhythmias. Data were analysed using Fisher's exact test with a p<0.05 as statistically significant. Results: 221 patients received an ICD during the study period, with follow-up data for a mean of 16 months (range 0–28 months): 78 of 117 primary prevention recipients had an indication according to both NICE and ESC guidelines and 39 complied only with ESC criteria. Two of these were lost to follow-up (one in each group). 17 of 78 (22%) patients in the NICE compliant group received appropriate therapy compared with 10 of 39 (26%) in the NICE non-compliant group. There was no significant difference between these two groups (Fisher's exact test; p = 0.64). 104 patients received an ICD as secondary prevention: one was lost to follow-up and 50 (48%) had appropriate therapy. The therapy delivered in each group is shown in the table. Conclusion: Patients who had an ICD implanted outwith NICE guidance received appropriate therapy as often as those within NICE guidance in the first 16 months after implantation. NICE guidance therefore fails to recommend ICD therapy to all patients who would benefit, and the less restrictive ESC guidelines may be more appropriate for clinical practice.